The "Wallpaper Effect" Revisited: Divergent Findings on the Effects of Intergroup Contact on Attitudes in Diverse Versus Nondiverse Contexts. (September 2017) - Schmid, Katharina; Wölfer, Ralf; Swart, Herman; Christ, Oliver; Al Ramiah, Ananthi; Vertovec, Steven; Hewstone, Miles
This article reexamines the so-called "wallpaper effect" of intergroup contact, which contends that for minority group members living in areas more densely populated by majority group members, intergroup contact fails to reduce prejudice. We tested this claim in five studies, using data from five countries, two types of contexts, a range of measures, and involving different minority versus majority groups. Using multilevel cross-level interaction models, we considered whether effects of contact on outgroup attitudes were moderated by relative outgroup size. Results failed to replicate the previously reported findings, revealing, by and large, nonsignificant cross-level moderation effects; instead, we witnessed consistent positive contact effects on attitudes. Findings are discussed against the backdrop of recent research on the consequences of diversity, as well as context-based considerations regarding minority versus majority constellations. We also discuss some exceptions to our findings that emerged for some respondent groups and contexts across the five studies.